Imam Syatbi (Biografi dan Pemikirannya) - Thalhah Thalhah (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2004)
Syatibi was born and lived in Granada As a great reformist, he received some acknowledgement lqbal who refer him as developer of Islamic law in Pakistan, Rasyid Ridha who put him in line with Ibn Khaldun and Fazlur Rahman who called him a brilliant jurist This is for his thought on purpose of law (maqashid al-syari), and virtue (maslahat): that the main goal of Islamic law is virtue. Islamic law is not merely formal law, there exists spirit of law instead.